2016
DOI: 10.1111/ijlh.12489
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenia and neutrophil‐to‐lymphocyte ratio in a healthy Korean population: race and sex should be considered

Abstract: Our data indicate that the normal range of absolute neutrophil counts should be adjusted and cutoff values for neutropenia should be re-established according to sex and race. NLR and PLR cutoff values for disease evaluation should be established separately according to race and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 24 publications
2
12
2
Order By: Relevance
“…The NLR reference range has not been extensively studied. Kweon et al reported that the median NLR values are 1.53 and 1.54 for Korean men and women, respectively, and the upper 2.5 th percentile values are 3.51 and 3.54, respectively [ 51 ]. In Belgian subjects, the upper limit of the 95% CI is 3.53, with a mean of 1.65 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NLR reference range has not been extensively studied. Kweon et al reported that the median NLR values are 1.53 and 1.54 for Korean men and women, respectively, and the upper 2.5 th percentile values are 3.51 and 3.54, respectively [ 51 ]. In Belgian subjects, the upper limit of the 95% CI is 3.53, with a mean of 1.65 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a multicenter cross-sectional study of a healthy Indian population, Sairam et al [ 39 ] found lower levels of platelets in elderly people. Kweon et al [ 40 ] investigated median PLRs in a healthy Korean population and suggested that the PLR cutoff values for disease evaluation should be established separately according to age. Therefore, we should consider age when evaluating the relationship between the PLR and mortality among critically ill patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 26 cross-sectional or longitudinal studies demonstrated that increased levels of C-reactive protein (CRP) in schizophrenic patients was parallel to the severity of positive symptoms but not associated with the initiation of antipsychotic medication; and the researchers suggested that CRP might be a marker of systemic low-grade inflammation [30]. The NLR can be derived from the white blood cell count, and is inexpensive, replicable and also it has been found to be significantly correlated with CRP [31]. It has been suggested as a new indicator of low-grade inflammation and a predictor of clinical outcomes inneuroimmune disorders [10,11].…”
Section: Discussionmentioning
confidence: 99%